A study of customer retention and churn rate management through data mining and customer profiling of Malaysian mobile user - Ong, Derek Lai Teik *; Tan, Madeline Su Lin *; Andrews, Elizabeth * (2012)
This study aims to investigate the needs and wants of prepaid mobile service subscribers in Malaysia and identify usage patterns of industry churners, ultimately to offer the right product and value to target customers within a highly competitive market. This paper discusses the challenges faced by mobile companies in relation to high churn rates (sometimes called attrition rate), maintaining customer loyalty and the presence of stiff competition. Data was collected through database extraction from a telecommunication company in Malaysia which includes available demographic and behavioral data of the subscribers. Apriori association algorithm was employed to determine product bundling and C&R decision trees were used for customer profiling. It was discovered that there were three main product bundles subscribed by the prepaid mobile consumers. A brief look at the behavioral usage pattern of churners was also discussed. These information help mobile service providers to be more aware of their customer needs and to intelligently predict potential market churners.